Promoting brown and beige adipocyte biogenesis through the PRDM16 pathway - Kajimura, S (Int J Obes Suppl, 2015)
Obesity develops from a chronic energy imbalance in which energy intake exceeds energy expenditure. As brown adipose tissue (BAT) dissipates energy and produces heat, increasing energy expenditure via BAT thermogenesis may constitute a novel therapeutic intervention for the treatment of obesity and obesity-related diseases. Studies over the past few years have identified key regulatory molecules of brown and beige adipocyte biogenesis, including a dominant transcriptional co-regulator PRDM16 (PR domain containing 16) and its co-factors, which allows for engineering functional BAT by genetic approaches. A next step toward the goal of promoting BAT thermogenesis by pharmacological approaches necessitates a better understanding of the enzymatic components and signaling pathways for brown and beige adipocyte development. This review covers recent advances regarding this topic, with a special emphasis on the PRDM16 transcriptional pathway.